Prevalence of non-motor symptoms in Parkinson’s disease - C., Shakthi; B., Sritharan; M., Muthuveeran; M. R., Manivannan; C., Justin; D., GanesaPandian (International Journal of Research in Medical Sciences, 2019)
Background: Parkinson’s disease is a common neurodegenerative movement disorder characterised by motor symptoms of rest tremor, bradykinesia, rigidity and postural instability and non-motor symptoms (NMS) which include neuropsychiatric symptoms, sleep disturbances, autonomic symptoms, sensory symptoms and symptoms of mixed aetiology. Parkinson’s Disease Non Motor Group (PD-NMG) devised a comprehensive clinic-based self-completed NMS questionnaire that allows easy identification of NMS by the physician. Most NMS have a poor response to dopaminergic therapy as it is due to dysfunction of the serotonergic and noradrenergic pathways. Treatment of these nonmotor symptoms help in improving the quality of life in patients with Parkinson’s disease. Methods: There were 100 patients with Parkinson’s disease who had presented to our neuromedicine movement clinic were included in the study. Patients were diagnosed as PD based on UK Parkinson’s disease brain bank criteria. The inclusion criteria were diagnosis as PD, age >18 yrs, inclusion of both males and females and consent for the study. Patients with atypical parkinsonism and secondary parkinsonism, stroke, intake of antipsychotics were excluded from the study. Non motor symptom questionnaire was given to the study group and frequency of occurrence of each non motor symptoms and their predominance in both males and females were studied. The frequency of each NMS was calculated by computing the number of yes response and calculating the percentage related to the number of patients in the sample. Analysis was done to calculate the frequency of all NMS among the enrolled patient. Results: Nocturnal sleep disturbances (43%) were most common followed by constipation (29%).The most common non motor symptoms in males were constipation (20%), urinary urgency (18%) and nocturia (11%).The most common non motor symptoms in females were nocturnal sleep disturbance (25%), feeling sad (19%), unexplained pains (17%) and being anxious (13%). Conclusions: Non motor symptom questionnaire helps in screening patients with Parkinson’s disease of non-motor symptoms and aims at providing holistic treatment improving the quality of life.